Microglia integration into human midbrain organoids leads to increased neuronal maturation and functionality. Issue 7 (9th March 2022) - Sabate‐Soler, Sonia; Nickels, Sarah Louise; Saraiva, Cláudia; Berger, Emanuel; Dubonyte, Ugne; Barmpa, Kyriaki; Lan, Yan Jun; Kouno, Tsukasa; Jarazo, Javier; Robertson, Graham; Sharif, Jafar; Koseki, Haruhiko; et al.
Abstract: The human brain is a complex, three‐dimensional structure. To better recapitulate brain complexity, recent efforts have focused on the development of human‐specific midbrain organoids. Human iPSC‐derived midbrain organoids consist of differentiated and functional neurons, which contain active synapses, as well as astrocytes and oligodendrocytes. However, the absence of microglia, with their ability to remodel neuronal networks and phagocytose apoptotic cells and debris, represents a major disadvantage for the current midbrain organoid systems. Additionally, neuroinflammation‐related disease modeling is not possible in the absence of microglia. So far, no studies about the effects of human iPSC‐derived microglia on midbrain organoid neural cells have been published. Here we describe an approach to derive microglia from human iPSCs and integrate them into iPSC‐derived midbrain organoids. Using single nuclear RNA Sequencing, we provide a detailed characterization of microglia in midbrain organoids as well as the influence of their presence on the other cells of the organoids. Furthermore, we describe the effects that microglia have on cell death and oxidative stress‐related gene expression. Finally, we show that microglia in midbrain organoids affect synaptic remodeling and increase neuronal excitability. Altogether, we show a more suitable system to further investigate brain development, as well as neurodegenerative diseases and neuroinflammation. Main Points: Microglia were efficiently integrated into midbrain organoids. Oxidative stress‐related genes are downregulated in organoids with microglia. Gene expression and electrophysiology suggest a better neuronal functionality upon coculture.